2020
DOI: 10.3389/fonc.2020.586268
|View full text |Cite
|
Sign up to set email alerts
|

Five microRNAs in Serum Are Able to Differentiate Breast Cancer Patients From Healthy Individuals

Abstract: Breast cancer is the cancer with the most incidence and mortality in women. microRNAs are emerging as novel prognosis/diagnostic tools. Our aim was to identify a serum microRNA signature useful to predict cancer development. We focused on studying the expression levels of 30 microRNAs in the serum of 96 breast cancer patients vs. 92 control individuals. Bioinformatic studies provide a microRNA signature, designated as a predictor, based on the expression levels of five microRNAs. Then, we tested the predictor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…These findings underscore the link between miR-200 and metastatic spread and indicate them as markers for early detection of metastatic disease and prognosis. However, this assertion is tempered by results of recent investigation of serum markers of breast cancer that included miR-200 members in its list of interrogated miRNAs, which indicated an association between high serum levels of miR-141 and better survival [ 135 ]. This study also proposed a 5-miRNA panel for serum-based detection of breast cancer which however did not include miR-141 or other miR-200 members [ 135 ].…”
Section: Circulating Mir-200 As Biomarkersmentioning
confidence: 99%
“…These findings underscore the link between miR-200 and metastatic spread and indicate them as markers for early detection of metastatic disease and prognosis. However, this assertion is tempered by results of recent investigation of serum markers of breast cancer that included miR-200 members in its list of interrogated miRNAs, which indicated an association between high serum levels of miR-141 and better survival [ 135 ]. This study also proposed a 5-miRNA panel for serum-based detection of breast cancer which however did not include miR-141 or other miR-200 members [ 135 ].…”
Section: Circulating Mir-200 As Biomarkersmentioning
confidence: 99%
“…It was upregulated and associated with poor survival in metastatic breast cancer patients particularly in those with TNBC (29), but, on the other hand, it is among the most potent miRNAs repressing cell growth and counteracting estradiol-dependent cell proliferation (30). In our study a greater expression of miR-181a was positively associated with long-term fulvestrant bene t. Also on miR-16-5p literature data are somehow inconsistent since preclinical data support tumor suppressive properties but an increased expression in TNBC as compared to normal tissues has been found as well as either a down-or upregulation in the serum of breast cancer patients as compared to healthy controls (33,(35)(36)(37). In our study miR-16-5p was associated with a decreased probability of being progression-free at 18 months.…”
Section: Discussionmentioning
confidence: 59%
“…In our study we identi ed 9 miRNAs which were signi cantly and differently associated with 18-month PFS. Literature data provide evidence about 3 of these miRNAs (let-7c, miR-520d-3p, miR-181a) to be involved in HR+ABC (30)(31)(32)(33)(34)(35). In particular miR-520d-3p was among miRNAs which were downregulated upon estradiol stimulation in BCCL (30).…”
Section: Discussionmentioning
confidence: 96%
“…In our study we identified 9 miRNAs which were significantly and differently associated with 18-month PFS. Literature data provide evidence about 3 of these miRNAs (let-7c, miR-520d-3p, miR-181a) to be involved in HR+ ABC [30][31][32][33][34][35] . In particular miR-520d-3p was among miRNAs which were downregulated upon estradiol stimulation in BCCL 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study a greater expression of miR-181a was positively associated with long-term fulvestrant benefit. Also on miR-16-5p literature data are somehow inconsistent since preclinical data support tumor suppressive properties but an increased expression in triple negative breast cancer (TNBC) as compared to normal tissues has been found as well as either a down-or upregulation in the serum of breast cancer patients as compared to healthy controls 33,[35][36][37] . In our study miR-16-5p was associated with a decreased probability of being progressionfree at 18 months.…”
Section: Discussionmentioning
confidence: 99%